1999
DOI: 10.1016/s0893-133x(99)00068-8
|View full text |Cite
|
Sign up to set email alerts
|

CSF SNAP-25 in Schizophrenia and Bipolar Illness A Pilot Study

Abstract: Research efforts to identify and understand the In the past 20 years, scientists have conducted extensive research to identify the pathology and etiology of schizophrenia and bipolar illness. In schizophrenic subjects, neuroimaging and functional analysis has identified abnormalities in various brain structures (Nasrallah 1990). Neuropathological studies of schizophrenics have revealed brain changes ranging from loss of gray matter to disorganization of the normal neuronal architecture (Bloom 1993). More recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…SNAP25 can deliver neurotransmitter-containing vesicles to the inner plasma membrane. Human and animal studies indicate that SNAP25 is a risk factor for mental illness, such as SCZ (38,39). For the SNAP25 rs3746544 polymorphism, there have been two previous studies with positive results (47,48) in Europeans (Czechs and British populations) and one negative result (49) in Asians (Japanese).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SNAP25 can deliver neurotransmitter-containing vesicles to the inner plasma membrane. Human and animal studies indicate that SNAP25 is a risk factor for mental illness, such as SCZ (38,39). For the SNAP25 rs3746544 polymorphism, there have been two previous studies with positive results (47,48) in Europeans (Czechs and British populations) and one negative result (49) in Asians (Japanese).…”
Section: Discussionmentioning
confidence: 99%
“…A higher expression of GRIK3 has been found in SCZ cases compared to controls (37). SNAP25 encodes a protein that is implicated in the docking priming and fusion of the vesicles, which has been shown to be associated with SCZ (38,39). Association studies between the genetic polymorphisms of the aforementioned 7 genes and SCZ have been performed in different populations (Table I).…”
Section: Introductionmentioning
confidence: 99%
“…Ventricular CSF has a somewhat different expression of proteins compared to lumbar CSF [16] . Since it has a substantially lower protein level of both IgG and albumin (up to 9-fold) [17] , the CSF samples were not incubated with protein G as in a previous study [18] .…”
Section: Csf Collectionmentioning
confidence: 99%
“…A study indicated higher SNARE complex formation in the anterior frontal cortex samples obtained from patients who committed suicide . Investigation of CSF samples obtained from living patients indicated higher than expected levels of SNAP-25, and some correlations with symptom severity (Thompson et al, 2003;Thompson et al, 1999). Genetic studies in humans provide indirect evidence for a role for SNARE proteins in brain function, and in psychiatric illness.…”
Section: Introductionmentioning
confidence: 96%